2018
DOI: 10.1051/e3sconf/20184400004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of passive house technology on time and cost of construction investment

Abstract: Due to the changes in the energy standards for housing in Poland there are many concerns. Is the standard required by the regulation achievable and if it is, then at what cost? There are many solutions to construct a building in line with the requirements of passive house technology. They are differentiated by price and time required for implementation. This study is based on the solution proposed by one of Polish companies, offering technologically integrated products allowing, according to the producer, to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Alanne et al [12] investigated different heat loss properties of the building envelope and various service system options in educational buildings in Finland and showed that the difference in construction costs (above the reference) is 30-65 €/m 2 . Apollo and Miszewska-Urba ńska [13] analysed the influence of passive house technology on the time and cost of the construction investment and showed that the application of passive house technology increases the investment cost by 38% more than the conventional technology. Nevertheless, the cost of an energy efficient building is not always higher than that of a conventional building.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alanne et al [12] investigated different heat loss properties of the building envelope and various service system options in educational buildings in Finland and showed that the difference in construction costs (above the reference) is 30-65 €/m 2 . Apollo and Miszewska-Urba ńska [13] analysed the influence of passive house technology on the time and cost of the construction investment and showed that the application of passive house technology increases the investment cost by 38% more than the conventional technology. Nevertheless, the cost of an energy efficient building is not always higher than that of a conventional building.…”
Section: Literature Reviewmentioning
confidence: 99%